Factors Affecting Menopause - Rijanto, Rijanto; Jeniawaty, Sherly (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Background: The age of menopause between woman and other women is not similar and it depends on the factors that influence it. Some opinions suggest that menopause occurs at the age of 48-50 years, including in the climacteric period which is a syndrome of endocrine, somatic, and psychic changes at the end of the fertile / reproductive period (40-65 years). Objective: Analyze factors affecting menopause to woman. Methods: The type of this conducted research was survey research that was descriptive analytic. Population in this research was all women who aged 45-50 years at BPS Media in Surabaya, and there were 46 women. Multivariate analysis was conducted by utilizing multiple logistic regression in order to predict how far the value of dependent variable when the value of independent variable changed. Results: Multiple logistic regression analysis was performed to determine the effect of independent variables simultaneously to the dependent variable. The variable of menarcheage, job status, number of children, age in childbirthing for last child, contraception use, smoking, alcohol consumption, and disease history had p <0.25 and treated simultaneously by using forward stepwise method with 95% of confidence level. From the result of multiple logistic regression analysis, it turned out that the variable of menarche age (p = 0.762), the last childbirth age (p = 0.231), alcohol consumption (0.659), and disease history (p = 0.711) had no significant influence which p value was greater rather than Î± value (0.05), thus, it was excluded from the multiple logistic regression analysis model. Based on the result of multiple logistic regression analysis, the employment status, the number of children, the use of contraception, and smoking correlated with the occurrence of menopause with the probability value was smaller than Î± value  (0.05), which work status was p = 0.033, p = 0.003, and smoking was p = 0.003. Conclusion: From the result of multiple logistic regression analysis, it was found that job status, number of children, contraception use, and smoking were simultaneously correlated with the occurrence of menopause, which each variable had a smaller probability value than Î± value (0.05), employment status (p = 0.033), number of children (p = 0.000), contraception use (p = 0.004), and smoking (p = 0.003). From the results of logistic regression equations, it was known that the probability of premature menopause was occurred if woman who worked, had children less than 4 children, never used contraception, and ever smoked were 0.95 or 95%.